2011
DOI: 10.1371/journal.pone.0024979
|View full text |Cite|
|
Sign up to set email alerts
|

Gαi2- and Gαi3-Specific Regulation of Voltage-Dependent L-Type Calcium Channels in Cardiomyocytes

Abstract: BackgroundTwo pertussis toxin sensitive Gi proteins, Gi2 and Gi3, are expressed in cardiomyocytes and upregulated in heart failure. It has been proposed that the highly homologous Gi isoforms are functionally distinct. To test for isoform-specific functions of Gi proteins, we examined their role in the regulation of cardiac L-type voltage-dependent calcium channels (L-VDCC).MethodsVentricular tissues and isolated myocytes were obtained from mice with targeted deletion of either Gαi2 (Gαi2 −/−) or Gαi3 (Gαi3 −/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 47 publications
3
20
2
Order By: Relevance
“…Several studies have shown that knocking out one isoform of Giα protein upregulates the expression of other isoforms of Giα protein in knockout mice . In the current study, however, the effect of antisense was very specific because Giα‐2 antisense attenuated the expression of the Giα‐2 protein without affecting the expression of Giα‐3 protein, and Giα‐3 antisense attenuated the expression of Giα‐3 and not Giα‐2 protein.…”
Section: Discussioncontrasting
confidence: 62%
“…Several studies have shown that knocking out one isoform of Giα protein upregulates the expression of other isoforms of Giα protein in knockout mice . In the current study, however, the effect of antisense was very specific because Giα‐2 antisense attenuated the expression of the Giα‐2 protein without affecting the expression of Giα‐3 protein, and Giα‐3 antisense attenuated the expression of Giα‐3 and not Giα‐2 protein.…”
Section: Discussioncontrasting
confidence: 62%
“…Our detailed analysis of G protein levels in the G␣ i2 genetargeted mouse lines corroborates significant upregulation of G␣ i3 (about 45%) in the global G␣ i2 -deficient mice, which has also been described for other tissues and organs (6,17,39,40). In contrast to the global G␣ i2 -deficient islets, the G␣ i3 protein levels were unchanged in G␣ i2 ␤cko islets.…”
Section: Discussionsupporting
confidence: 86%
“…2), and this may also account for some of the enhanced responses observed in Ga i3 deficiency. Further studies will be needed to test the possibility of an antagonistic interplay between Ga i2 and Ga i3 in the transendothelial migration of neutrophils, as has been suggested previously for CXCR3-mediated signaling in T cells (41) and for the G i -specific regulation of calcium channels in cardiomyocytes (42,43).…”
Section: Discussionmentioning
confidence: 93%